Development of Students' Intellectual Area - as a Pedagogical Problem (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, a logical thought is made about intelligence and its essence, intellectual and creative activity, metacognitive experience, and the formation and management of intellectual activity, and some pedagogical problems that should be paid attention to in this regard are analyzed.